Development of a Mobile Pocket Book with a Problem-Based Learning Model to Improve Students Physics Literacy - Magdalena, Magdalena; Harjono, Ahmad; Busyairi, Ahmad; Ayub, Syahrial (Jurnal Pijar Mipa, 2024)
Physics learning, especially on heat, often faces various obstacles, such as low student literacy and limited interactive learning media. Mobile pocketbooks come as one of the solutions to overcome these problems. This application-based digital learning media is designed to provide easy access to students ' learning materials through mobile devices. The mobile pocketbook is an application-based digital learning media designed to facilitate students' flexible access to learning materials through mobile devices. Using the Problem-Based Learning (PBL) model in the mobile pocketbook supports Active Learning, where students solve real problems to improve concept understanding and science literacy. This research aims to develop and test the validity and practicality of the product in the form of a mobile pocketbook as a medium to support physics learning, especially on heat material. The research method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). However, due to time and cost constraints, this research did not reach the dissemination stage. Product validity was evaluated through assessments from experts and practitioners. The results of the expert assessment showed a validity level of 92.50%, while the practitioner gave a validity value of 96.25%, which indicated that the product was very valid. In addition, the product practicality test was evaluated through a questionnaire given to students and teachers. The questionnaire’s results show that this media is very practical, with a practicality value from the students' response of 90.76% and the teacher reaching 96.47%. Thus, the mobile pocketbook was designed using a problem-based learning model to improve students' physics science literacy. The results showed that this media is valid and practical for enhancing students' understanding of physics material, especially the concept of heat, as evidenced by the average practicality value of 93.61%. Therefore, this mobile pocketbook is expected to be one of the learning media innovations that can improve the quality of physics learning in schools.